Prevalence of Coxiella burnetii infection (the causative agent of Q-fever) in the residents of the republic of Tatarstan - N. K. Tokarevich; G. Sh. Isaeva; I. A. Karmokov; R. R. Baimova; D. I. Grechishkina; I. S. Lyzenko; E. G. Riabiko; O. A. Freylikhman; E. S. Khalilov; G. F. Gilyazutdinova; R. A. Isaeva; T. A. Savitskaya; et al. (Журнал инфектологии, 2025)
The official statistic data on Q fever cases in Russia do not reflect the real spread of this infection. One of the reasons for Q fever significant underdiagnosis is the difficulty of its clinical diagnosis due to the pronounced polymorphism of the disease manifestations and the absence of pathognomonic symptoms.The study objective was to determine the level of seroprevalence of the population to the Coxiella burnetii in the Republic of Tatarstan.Materials and methods. ELISA was used to detect IgG antibodies to Q fever pathogen in blood sera sampled from volunteers (480 samples). The volunteers whose serum samples proved to be IgG–positive were offered a questionnaire intended to reveal the risk factors for contamination with the Q fever causative agent, and their blood was re-sampled after 5-6 months in order to determine the duration of IgG antibodies persistence.Results. IgG antibodies to C. burnetii were revealed in 7.7% of the surveyed volunteers. The re-examination of seropositive persons revealed the corresponding antibodies in 82% of them. Based on the results of the questionnaire survey it was concluded that the majority of the respondents were involved in pet care or farm animals keeping, and 80% of the respondents had suffered febrile illness during past two years. The highest seroprevalence was detected in humans over 40, while more often in women than in men.Conclusion. The results obtained indicate the existence of active foci of Q fever on the territory of the Tatarstan Republic, where residents come into contact with C. burnetii. It is likely that ELISA is a useful assay for detecting IgG antibodies over rather long period of time after contamination with the causative agent of Q fever. The revealed irregularity of the territorial distribution of infected residents argues for the advisability of further research in order to identify the infection sources, first of all, in areas with high seroprevalence. The detected rather high C. burnetii seroprevalence in the population of the Republic of Tatarstan in the absence of reported Q fever incidence bear witness to significant underdiagnosis of the infection, and hence justifies the needs of effective preventive measures development taking into account the local conditions.